Canonical Correlation among Paddy Growers’ Soil Health Card Knowledge Perception, Adoption in Andhra Pradesh - CHUNDRU, RAMYA MADHURI; Akkamahadevi Naik; Ashok Kumar; Chitrasena Padhy; Soumik Ray (Indian Journal of Extension Education, 2024)
The research employs canonical correlation analysis to explore the interplay between Soil Health Card (SHC) knowledge, perception, and adoption among paddy growers in North Coastal Andhra Pradesh for the years 2023-2024. Effective paddy cultivation demands careful management throughout all stages—from transplanting to post-harvest—tailored to local conditions. In response to soil degradation and the need for improved agricultural productivity, the Gujarat administration launched the Soil Health Card initiative. This study aims to reveal the relationships and factors influencing SHC utilization in the region. By examining these variables, the research seeks to enhance agricultural practices and promote sustainable farming. The findings will provide valuable insights for authorities, rural extension centres, and other stakeholders involved in SHC programs. Understanding the factors that drive or hinder SHC adoption will help develop targeted strategies to increase awareness, shift perceptions, and encourage broader implementation among paddy growers. Ultimately, this research supports the goal of advancing soil health management practices and fostering agricultural sustainability in Andhra Pradesh.